Case Study on Geoscience Teaching Innovation: Using 3D Printing to Develop Structural Interpretation Skill in Higher Education Levels - Piyaphong Chenrai; Piyaphong Chenrai (Frontiers in Earth Science, 2021)
Applying three-dimensional (3D) printing technology to a geoscience classroom provides an alternative way to teach students. This brief report describes an educational innovation for the geoscience classroom by 3D printing technology to develop structural interpretation skill in high education level in Thailand. In comparison to traditional classrooms, this teaching method enables students to more easily comprehend how geological structures and features occur in nature through a project-based learning in seismic interpretation course. 3D printing models are constructed based on student interpretation through three different software packages. The observations in this study indicate that the ability to create the 3D models based on digital seismic data can enhance structural interpretation skill of students. The benefit of freely orientating and viewing in different angles of the 3D models leads to a construction of cognitive abstract space and spatial visualization ability. Therefore, 3D printing technology plays an important role in changing and developing the geoscience education system in Thailand at present and in the future. This teaching method could potentially benefit any science classroom and have applications in other disciplines requiring similar skill.